Peningkatan Pendidikan Keagamaan Anak melalui Media Pembelajaran di Desa Menuran - Febryan Hidayat; Sukari Sukari; Muttorik Alil Abasir (Jurnal Medika: Medika, 2025)
The quality of children's religious education at the community level is greatly influenced by the availability of adequate learning media. However, in many institutions such as TPA, elementary schools, and RA/BA, religious learning media are still limited, so learning tends to take place passively and less interestingly. Based on these conditions, this community service activity aims to improve the quality of children's religious learning through learning media procurement strategies. The activity was carried out by the PKM MABAIS-IIM Surakarta Team in three educational institutions in Menuran Village, Baki District, Sukoharjo Regency. The methods used include field observations, coordination with institutions, raising donations, distributing learning media, and evaluating the impact of the programme. The results showed that after the procurement of media such as Iqra' books, Islamic stories, stationery, and folding tables, there was a significant increase in children's participation and enthusiasm for learning. The learning process became more interactive and interesting. This programme proves that the provision of learning media is an effective and applicable strategy to improve the quality of religious education. It is hoped that this activity can become a model that is replicated sustainably in various other areas with similar conditions.